Protocol for a randomised controlled trial of continuous infusions of vancomycin to improve the attainment of target vancomycin levels in young infants: The VANC trial. Issue 11 (3rd November 2018) - Gwee, Amanda; Cranswick, Noel; Donath, Susan M; Hunt, Rodney; Curtis, Nigel
Abstract : Introduction: Vancomycin is frequently used in the treatment of late-onset sepsis in young infants and is routinely administered as intermittent infusions (IIV); however, existing IIV dosing guidelines achieve target vancomycin levels in less than half of infants. Continuous infusions of vancomycin (CIV) are an attractive alternative as adult studies report a higher attainment of target vancomycin levels, simpler drug monitoring and fewer drug side effects. Methods: This is a multicentre, randomised controlled trial in which 200 young infants (aged 0–90 days) requiring vancomycin will be randomised to CIV or IIV for a duration determined by the treating clinician. Vancomycin levels will be measured immediately after the first dose in both arms. Trough and peak levels will be determined in the IIV arm and steady-state levels 18–30 hours after commencement of infusion will be measured in the CIV arm. Full blood count, urea and electrolytes, and C reactive protein level will be monitored throughout treatment. For all Gram-positive bacteria isolated from blood culture, a vancomycin Etest will be done to determine the minimum inhibitory concentration of the bacterium. Analysis: Primary outcome: the proportion of infants with levels within target range at their first steady-state concentration. Secondary outcomes: (1) the proportion of drug-related adverse effects; (2) the time to achieve target levels in the blood; (3) the pharmacodynamics of vancomycin (using non-linear mixed effect modelling). Ethics and dissemination: The study has been approved by The Royal Children's Hospital Melbourne Human Research Ethics Committee (HREC) (No. 34030) and the South Eastern Sydney Local Health District HREC (SSA 16/G/335). Results will be published in a peer-reviewed journal. Trial registration number: NCT02210169 .